2013
DOI: 10.1590/s0004-27302013000800009
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone secretion in patients with septic shock: a prospective study

Abstract: Objective: To assess serum levels of the main factors that regulate the activation of the zona glomerulosa and aldosterone production in patients with septic shock, as well as their response to a high-dose (250 μg) adrenocorticotropic hormone (ACTH) stimulation test. Subjects and methods: In 27 patients with septic shock, baseline levels of aldosterone, cortisol, ACTH, renin, sodium, potassium, and lactate were measured, followed by a cortrosyn test. Results: Renin correlated with baseline aldosterone and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Prior work suggests that decreased effective circulating volume and renin activity, rather than potassium or adrenocorticotropin, are the primary regulators of the aldosterone level during critical illness. 41 Our results suggest that for the FACTT patients with higher initial aldosterone levels (lower effective circulating volume), the potential risks of fluid administration were balanced by the potential benefits in improving effective circulating volume. In contrast, for FACTT patients with lower initial aldosterone levels (higher effective circulating volume), diuresis and prevention of fluid administration appear to have improved mortality.…”
Section: Discussionmentioning
confidence: 69%
“…Prior work suggests that decreased effective circulating volume and renin activity, rather than potassium or adrenocorticotropin, are the primary regulators of the aldosterone level during critical illness. 41 Our results suggest that for the FACTT patients with higher initial aldosterone levels (lower effective circulating volume), the potential risks of fluid administration were balanced by the potential benefits in improving effective circulating volume. In contrast, for FACTT patients with lower initial aldosterone levels (higher effective circulating volume), diuresis and prevention of fluid administration appear to have improved mortality.…”
Section: Discussionmentioning
confidence: 69%
“…The plasma concentrations of aldosterone were found to be unexpectedly low in meningococcal sepsis compared with ICU admissions for other reasons ( 141 ). Lower than expected aldosterone levels have also been reported in adults’ septic shock ( 142 , 143 ). Inappropriately low aldosterone levels during septic shock were associated with increased ICU length of stay, an increased incidence of acute kidney failure ( 144 ), and increased mortality ( 145 ).…”
Section: Immunomodulation In Sepsismentioning
confidence: 74%
“…Animal studies found an association between sepsis and the downregulation of the MR in endothelial cells [50], and mineralocorticoid supplementation lowered IL-6 levels, hastened shock reversal, and improved survival [51,52]. Some clinical studies also revealed inappropriately low aldosterone levels in patients with septic shock, suggesting an impaired adrenal synthesis of aldosterone, that might be associated with increased mortality [41,53]. Although the direct effect of mineralocorticoids in septic patients has not been fully elucidated, our results support a recommendation for the dual administration of hydrocortisone and fludrocortisone to patients with septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…While hydrocortisone has been extensively examined in sepsis, fludrocortisone has been used for patients with aldosterone deficiency, and the dual administration of these two medications is recommended for some patients with primary adrenal insufficiency [39,40]. Considering that patients with septic shock have been found to have unexpectedly low aldosterone levels due to HPA axis abnormalities [41], dual treatment with hydrocortisone and fludrocortisone should be further validated as a type of corticosteroid treatment for septic shock.…”
Section: Introductionmentioning
confidence: 99%